The nature and quality of support from informal networks for informal caregivers of low-grade glioma patients: a qualitative analysis within the ways ahead study - Murrell, Andrew James; Rimmer, Ben; Dutton, Lizzie; Lewis, Joanne; Burns, Richéal; Gallagher, Pamela; Williams, Sophie; Araújo-Soares, Vera; Finch, Tracy; Sharp, Linda (European journal of cancer care, 2023)
Objective. Those closest to the patients with low-grade glioma (LGG) often become informal caregivers (ICs). Caregiving demands can impact ICs’ wellbeing, meaning they themselves may require support. We explored the nature and quality of support from informal networks for ICs of LGG patients. Methods. In this cross-sectional qualitative study, semistructured interviews were conducted with individuals from the United Kingdom who currently, or in the past five years, informally cared for someone diagnosed with an LGG. Interviews explored ICs’ experiences of receiving support from informal networks. Thematic analysis was undertaken. Results. Nineteen ICs were interviewed (mean age 54.6 years; 5 males, 14 females). ICs received multiple forms of support from their informal networks: emotional (e.g., “opportunities to talk”), instrumental (e.g., “opportunities for relief”), information (e.g., “information from network contacts”), and appraisal (e.g., “comparisons with similar others”). Networks comprised strong/familiar (e.g., close friends) and weaker/unfamiliar (e.g., other ICs) ties. Supportive networks were perceived to help protect ICs’ wellbeing. Participants perceived challenges such as poor understanding and unsolicited advice to weaken the quality of support. Conclusion. Informal networks can provide wide-ranging support for ICs of the LGG patients. Different supports may be sought or provided from different contacts, highlighting the importance and value of extended networks.
Veröffentlicht: 29. Juli 2023
Gesehen am 06.10.2023